KETERLIBATAN PENARI USIA MUDA DI BATAM TERHADAP EKSISTENSI TARI JOGI - Shaesa, Gilda Nurul (Universitas Negeri Semarang, 2020)
Jogi dance is a dance originating from the Riau Islands, Batam. The existence of Jogi dance first appeared in Batam and was danced with Malay forms, motifs, and movements. The Jogi dance was originally danced by a young Malay female dancer from Long Island. Young female dancers aged 15-18 years. Young age is the age when someone is said to have passed puberty and has become a teenager. The purpose of this research is to find out the reason for the existence of Jogi dance in young dancers in Batam today. The research method used is qualitative by conducting observations, interviews, literature studies, and documentation studies from Koroegrafer and Dancers who dance Jogi in Batam. The results of this study can be concluded that the involvement of young dancers in Batam towards the existence of Jogi dance still exists today, with informants and successors and heirs who preserve Jogi. Keywords: Existence, Jogi, Young age